ANALISIS LAJU KOROSI KAWAT ORTODONTIK LEPASAN STAINLESS STEEL PADA MEDIA AIR KELAPA - Reysa Rosdayanti; Diana Wibowo; Fajar Kusuma Dwi Kurniawan (Universitas Lambung Mangkurat, 2018)
ABSTRACT Background: Stainless steel orthodontic wire is a material commonly used in orthodontic treatment, because its economical price and corrosion resistance. The corrosion-resistant of stainless steel orthodontic wire can be affected by foods or beverages that have low pH. The coconut water has a low pH. Corrosion that occurs in orthodontic wire causes roughness on the surface of the wire and fragility, thus affecting duration of treatment. Purpose: determine corrosion rate of stainless steel orthodontic wire after immersed with coconut water. Methods: This research is true experimental study with pre-test and post-test control group design using simple random sampling. Consist of 20 samples divided into 2 groups: immersion in coconut water (experimental group), and immersion in saline (control group). Corrosion rate used weight loss method. Results: Mean corrosion rate of stainless steel orthodontic wire after immersion used coconut water and saline that is 1,9484mpy and 0,2587mpy. Wilcoxon test before and after immersion in treatment group obtained result p=0,005 while in control group obtained result p=0,180. The comparison of corrosion rate between groups using Mann Whitney U test results obtained p=0.001. The results shows the rate of corrosion in experimental group used coconut water has a significant difference, the control group used saline there was no significant difference. Conclusion: The rate of corrosion of stainless steel orthodontic wire immersion with coconut water is greater than the rate of corrosion in saline solution immersion. ABSTRAK Latar Belakang: Kawat ortodontik stainless steel merupakan bahan yang umumnya digunakan pada perawatan ortodontik, karena harga ekonomis dan ketahanan korosi yang baik. Sifat tahan korosi pada kawat ortodontik stainless steel dapat dipengaruhi oleh makanan atau minuman yang memiliki pH rendah. Salah satu minuman yang memiliki pH rendah yaitu air kelapa. Korosi yang terjadi pada kawat ortodontik menyebabkan kekasaran pada permukaan kawat dan kerapuhan, sehingga mempengaruhi lama waktu perawatan. Tujuan: mengetahui laju korosi kawat ortodontik stainless steel setelah direndam dengan air kelapa. Metode: Penelitian ini merupakan penelitian true experimental dengan pre-test and post-test with control group design menggunakan simple random sampling. Terdiri dari 20 sampel yang terbagi dalam 2 kelompok: yaitu direndam air kelapa (kelompok perlakuan), dan larutan salin (kelompok kontrol). Perhitungan laju korosi menggunakan metode weight loss. Hasil: Rerata laju korosi kawat ortodontik stainless steel setelah direndam menggunakan air kelapa dan larutan salin yaitu 1,9484mpy dan 0,2587mpy. Uji Wilcoxon sebelum dan sesudah perendaman pada kelompok perlakuan diperoleh hasil p=0,005 sedangkan pada kelompok kontrol diperoleh hasil p=0,180. Hasil Perbandingan laju korosi antar kelompok menggunakan Uji Mann Whitney U diperoleh hasil p=0,001. Hal ini menunjukkan laju korosi pada kelompok perlakuan menggunakan air kelapa terdapat perbedaan bermakna, sedangkan pada kelompok kontrol menggunakan larutan salin tidak terdapat perbedaan bermakna. Kesimpulan: Laju korosi kawat ortodontik stainless steel yang direndam dengan air kelapa lebih besar dibandingkan laju korosi pada perendaman larutan salin.